Illumination Compensation of Facial Image Using Combination Algorithm for Face Recognition - Duong, Trong Luong; Hoang, Truong Kien; Nguyen, Thanh Cong; Nguyen, Thai Ha (Old Journal, 2020)
So far, biometric identification in general and facial recognition in particular are still being researched and developed for applying in several areas such as security, etc. In this paper, the authors study on some facial image recognition methods that have been researched and published in the world. On the basis of the remaining disadvantages of these published methods, we proposed an illumination compensation method of facial image using Combination Algorithm for face recognition. It is combination method of Singular Value Decomposition and Curvelet algorithm (SVD_C). The results of this proposed method are compared with the results of Global Adaptive Singular Value Decomposition in the Fourier domain method (GASVD_F) and Adaptive Singular Value Decomposition in the Wavelet domain method (ASVD_W) via recognition rate criterion RR (%). Experimental results validate the efficiency of the proposed method.